The effectiveness of home-based circuit training on cardiovascular and biochemical parameters, physical fitness and quality of life among overweight and obese patients with knee osteoarthritis and type 2 diabetes mellitus - Al-Mhanna, Sameer Badri Hadi (2024)
Knee osteoarthritis (Knee OA) is often associated with overweight/obesity and type 2 diabetes mellitus (T2DM). The additional weight from being overweight or obese increases stress on the knee joints, accelerating the development of osteoarthritis. Meanwhile, T2DM exacerbates inflammation, worsening knee pain in individuals with osteoarthritis. Regular exercise has been documented as a principal component of treatment strategy for Knee OA patients. However, there are currently no evidence-based exercise protocols for individuals with Knee OA and comorbidities such as overweight or obesity and T2DM. Thus, the present randomised controlled trial aimed to investigate the effectiveness of a 12-week home-based combined circuit of aerobic and resistance training on cardiovascular, biochemical, and physical fitness parameters and quality of life (QoL) among overweight/obese patients with Knee OA and T2DM. A total of 70 overweight/obese patients with Knee OA and T2DM were randomly assigned to the intervention group (n=35) or the control group (n=35). The participants in the intervention group performed a progressive protocol (seven exercises; 15–30 repetitions per exercise, 1 min passive rest between exercises; 2–4 rounds per session; 20–60 min total session duration). Blood was obtained for determination of lipid profile, glycemic control, oxidative stress marker, an inflammatory marker, liver and renal function from both the groups at pre- and post-intervention. Meanwhile, cardiovascular, and physical fitness parameters as well as level of pain and QoL score were assessed from both the groups at pre-, mid and post-intervention. The present study demonstrated that 12-week home-based circuit training significantly improved systolic blood pressure (SBP), diastolic blood pressure (DBP), body mass index (BMI), fasting lipid profile (FLP), glycated haemoglobin (HbA1c), fasting blood sugar (FBS), Interleukin 6 (IL-6), superoxide dismutase (SOD) and liver function test (LFT) in the intervention group compared to the control group. Meanwhile, physical fitness including the 6-Minute Walking Test (6-MWT), peripheral oxygen saturation (SpO2), 30-second chair stand test (30CST), Timed Up and Go test (TUG), level of pain (VAS score) and QoL score were significantly improved in the intervention group compared to the control group. The improvements in these parameters may be attributed to the synergistic effects of both aerobic and resistance training, which target cardiovascular health, biochemical markers, and physical fitness. These were achieved by reducing oxidative stress and inflammation resulting in decreased pain levels and ultimately improving QoL. These findings emphasise the significant impact of home-based circuit training as adjuvant therapy in enhancing QoL among overweight/obese patients with Knee OA and T2DM. However, further studies are needed to determine the molecular changes associated with combined circuit training, contributing to a more comprehensive understanding of its effects.